Hemispherotomy in the surgical treatment of severe symptomatic epilepsy - Kostiuk, Kostyantyn R.; Cheburakhin, Valeriy V.; Buniakin, Viacheslav M. (Ukrainian Neurosurgical Journal, 2019)
Purpose. To evaluate the efficacy of peri-insular functional hemispherotomy (FH) for patients with severe drug-resistant epilepsy. Materials and Methods. Nine patients underwent peri-insular functional hemispherotomy. The patients included 1 adult (11.1 %) and 8 (88.8 %) children. Patients’ age ranged from 4 to 23 years (mean 9.9 ± 4.2 years). Epilepsy duration ranged from 1.5 to 16 years (mean 7.1 ± 3.1 years), mean seizures frequency was 12.9 ± 6.8 per day; before treatment patients used on average 5.1 ± 2.6 antiepileptic drugs. Diffuse injury of one hemisphere and contralateral hemiparesis were observed in all cases. Follow-up lasted from 1 to 17 months (mean 9.6 ± 1.4 months). Three (33.3 %) patients experienced Rasmussen’s encephalitis, 2 (22.2 %) had multi-lobar cortical malformation, 2 (22.2 %) had complications associated with intracerebral hemorrhage, 1 (11.1 %) patient represented with hypoxic-ischemic encephalopathy and 1 (11.1 %) patient experienced epilepsy associated with PNET resection, chemotherapy and local radiation. Results. After FH, 7 (77.7 %) children became seizure-free (Engel Class I A), seizure recurrence was observed in one (11.1 %) case in 6 months after surgery. Perioperative complications with following death occurred in one case (11.1 %). Hydrocephalus, which required shunting developed in one (11.1 %) child. Conclusion. Functional peri-insular hemispherotomy is an effective and safe method for surgical treatment of severe symptomatic epilepsy. Seizure cessation improves psychomotor development and diminishes neurocognitive disorders.